Aetiology and Antimicrobial Susceptibility Pattern of Bloodstream Infection among Patients with Chronic Kidney Diseases at a Tertiary Hospital in Tanzania (Tanzania Medical Journal, 2025)
BackgroundPatients with chronic kidney disease (CKD) are at an increased risk of acquiring bloodstream infections (BSI), particularly during dialysis. Using catheters and other invasive devices can serve as potential sources of infection. Resistant bacteria isolated from CKD patients with BSI significantly contribute to higher morbidity and mortality rates among these patients compared to the general population. MethodologyA laboratory-based cross-sectional study was conducted to analyse blood samples collected from patients with CKD at Muhimbili National Hospital, Dar es Salaam, Tanzania. Two pairs of blood culture bottles were collected from each patient and incubated in the BACTEC™ FX 04 system. Positive blood cultures were then sub-cultured on solid media for isolation. Gram staining and conventional biochemical tests were performed for bacterial identification. Antimicrobial susceptibility testing was carried out using the Kirby-Bauer disc diffusion method. The patient’s clinical data were obtained from their files. The Statistical Package for Social Sciences version 25 was used for data analysis. A p-value < 0.05 was considered statistically significant.ResultsTwo hundred participants with CKD receiving care at the nephrology and dialysis wards were enrolled. Most, 90/200 (45.0%), were adults aged 40-60, and males contributed 118/200 (59%). The prevalence of BSI among CKD patients was 75/200(37.5%). BSI was in 43/103 (41.7%) of participants receiving dialysis. Among the isolated bacteria, the Gram-negative bacteria were the predominant contributors, accounting for 43/75 (57.3%). The most frequent Gram-negative bacteria were Pseudomonas aeruginosa 13/43 (30.2%) and Escherichia coli 12/43 (27.9%). On the other hand, among the isolated Gram-positive bacteria, Coagulase negative staphylococcus (CoNS) was frequent, 23/32 (71.9%). Among the Gram-negative bacteria, Pseudomonas aeruginosa and Klebsiella pneumoniae demonstrated the highest resistance to ciprofloxacin, with rates of 75% and 90%, respectively. Meanwhile, Escherichia coli showed the highest resistance to ampicillin at 77%. Among Gram-positive bacteria, CoNS and Staphylococcus aureus exhibited the highest resistance to penicillin, with rates of 90% and 85.7%, respectively.Conclusion The present study has revealed that a significant proportion of CKD patients have BSI, and the isolated bacteria were resistant to commonly used antibiotics in our settings. These findings underscore the need to address antibiotic resistance through enhanced antimicrobial stewardship in our setting.